NIGERIA’S REVENUE ALLOCATION AND SUSTAINABLE ECONOMIC DEVELOPMENT - Omodero, Cordelia Onyinyechi (Annals of Spiru Haret University. Economic Series, 2018)
Abstract Sustainability of economic development in Nigeria has been a serious challenge despite the huge revenue allocated to the three tiers of the government on a monthly basis from the federation account. This recurring decimal has left the country in a pitiable condition with inadequate infrastructures to carry on economic activities. The study examines the extent to which revenue allocation enhances economic development using time series data obtained from CBN Statistical Bulletin which covered a period from 1981 to 2016. Ordinary Least Squares technique was employed and the findings revealed that FASG and NDSD have significant negative impact on PCI while FAFG has insignificant negative impact on PCI. On the contrast, the result shows that FALG has a robust significant positive impact on PCI. The study attributes this poor performance to misuse of resources and suggest that more stringent measures be employed by the government to fight graft in the public sector and among government officials. This will help to curb corrupt practices and ensure efficient and effective use of resources to boost economic development. Keywords: Revenue allocation, economic development, federation account, Resources, Nigeria.